La acción del Estado brasileño en relación a los migrantes bolivianos en Brasil : la cuestión del trabajo (in)documentado, refugio e inmigración económica [separata] - Ranincheski, Sonia Maria (2014)
From the beginning of the 21st Century, Brazil has been inserted in an agenda of international development and economic growth, presenting good labor conditions and global projections, representing a port of entry for various immigrant groups, including Bolivians, who are increasingly inserted into Brazilian society and economy—frequently illegally—and have influenced the role of the State and the diplomatic relationship between the country of origin and country of arrival of these immigrants. Hence, this article will deal with the insertion of Bolivian immigrants in Brazil through bibliographical, documental and statistical analysis, and will conclude on the specificities of this immigration on the Brazil-Bolivia relations and the projections for the first two decades of the new century.